Constructing a perceived and expected quality model between system supplier and end user to evaluate supply chain system. (9th August 2007) - Chang, Che-Wei; Wang, William Y.C.
An increasing emphasis on end-user demand and expanded development budgets in leading software development firms to increase the supply chain management system quality of their Products (PD). Decision makers apply quality standards and guidelines to evaluate software quality. However, standards and guidelines lack uniformity in software development firm quality and end-users' requirements. Accordingly, this study develops a grey decision making measurement model for evaluating the software quality of supply chain management system, to reduce the software quality of perceived and expected gap between the PD offered by a software development firm and end-users' requirements.